تحالف العمل الإشرافي و الفاعلية الذاتية الإرشادية للمتدربين : تضمينات لتطوير برامج تدريب طلبة الإرشاد - علاء الدين، جهاد محمود (جامعة السلطان قابوس, 2014)
تهدف الدراسة الحالية استناداً إلى نموذج بوردين (1983) لاستكشاف ما إذا كانت إدراكات المشرفين والمرشدين المتدربين لتحالف العمل الإشرافي (الأهداف والمهمات والرابطة العاطفية) تتنبأ بإدراكات المتدربين للفاعلية الذاتية الإرشادية لديهم. تألفت عينة الدراسة القصدية من (١٤٤) طالباً وطالبة من المرشدين المتدربين ومن (١٤) مشرفاً على هؤلاء الطلبة، في أربع جامعات حكومية في الأردن. أظهرت نتائج تحليلات الانحدار المتعدد أن عنصر الأهداف في علاقة تحالف العمل الإشرافي من وجهة نظر المتدربين، كان متنبئاً فريداً بالإدراكات الأكبر للفاعلية الذاتية الإرشادية لديهم، فقد فسر 11% من التباين في هذه الفاعلية الذاتية. كما تبين أيضاً أن إدراكات المشرفين للفاعلية الذاتية الإرشادية لدى متدربيهم قد فسرت 4% من التباين في الفاعلية الذاتية الإرشادية كما يدركها المتدربون. وباستثناء الرابطة العاطفية، تبين وجود فروق إحصائية دالة بين تقديرات مجموعتي المشرفين والمتدربين على مقاييس الفاعلية الذاتية الإرشادية وتحالف العمل الإشرافي. لصالح المتدربين الذين سجلوا درجات أعلى. تضم الدراسة تضمينات لعملية الإشراف ومقترحات لتحسينها ولدراسات مستقبلية. The study, based on the model of Bordin (1983), aims to explore whether the supervisors' and trainees' perceptions of supervisory working alliance (goals, tasks and emotional bond) predict trainees' perceptions of counseling self-efficacy. The study sample consisted of 144 undergraduate and graduate counseling students from four Jordanian state universities, and 14 supervisors of these students. Results of multiple regression analyses showed that from the viewpoint of the trainees, goals in the supervisory working alliance were the predictor of their counseling self-efficacy, and explained 11% of the variation in selfefficacy. In addition, supervisors' perceptions of the trainees' counseling self-efficacy, explained 4% of the variation in their trainees' perceptions of counseling self-efficacy. The study showed that trainees, compared to supervisors, had higher levels of counseling self-efficacy and supervisory working alliance perceptions, with the exception of the emotional bond. Findings highlight the importance of studying the supervisor-supervisee relationship in the context of counseling training programs. The study's results have implications for improving the supervision outcomes and proposals for future studies.
761452
Keywords: الطلاب المعلمون -- الارشاد التربوي -- الإرشاد النفسي -- المرشدون التربيون -- التدريب المهني -- الفاعلية الذاتية -- علم النفس التربوي -- المشرفون التربيون